Afterglow? The long-term influence of development finance institutions on firms' environmental, social and governance (ESG) policies - Stephane Kelk; James G. Copestake (University of Bath, Centre for Development Studies (CDS), 2022)
The paper enquires into the long-term effect of development finance institutions (DFI) on the environmental, social and governance (ESG) policies of companies in which they have invested. It does this through a review of secondary data on the ESG policies of ten companies operating in Africa and India that were recipients of investment from CDC, the DFI owned by the UK government. We find that most of these companies did invest in and maintain ESG initiatives, and two may also have affected the adoption of ESG policies by larger organisations that took them over. But while this is consistent with the hypothesis that CDC can contribute to strengthening ESG policies (particularly through equity investment) the evidence was mostly circumstantial rather than explicit. To help fill this evidence gap we suggest that CDC and other DFIs can be more open about the ESG goals linked to specific investments, and investees about what they subsequently do. And while it may still be almost impossible to establish causal links between DFIs and ESG activities statistically, there is scope for producing stronger evidence of the link using qualitative impact evaluation methods.
Keywords: 330; Additionality; CDC; development finance institutions; ESG policies; private sector development